2015
DOI: 10.5978/islsm.15-or-13
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of inflammatory response of wounds by antimicrobial photodynamic therapy

Abstract: Background and aims: Management of infections caused by Pseudomonas aeruginosa is becoming difficult due to the rapid emergence of multi-antibiotic resistant strains. Antimicrobial photodynamic therapy (APDT) has a lot of potential as an alternative approach for inactivation of antibiotic resistant bacteria. In this study we report results of our investigations on the effect of poly-L-lysine conjugate of chlorine p6 (pl-cp6) mediated APDT on the healing of P.aeruginosa infected wounds and the role of Nuclear F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 39 publications
1
22
0
1
Order By: Relevance
“…All showed that PDT reduced the infection. Specifically, the PDT‐treated infected wounds had significantly ( P < .05) lower bacterial counts at various time points than infected control wounds that had not been treated or had been treated with photosensitiser only or light only …”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…All showed that PDT reduced the infection. Specifically, the PDT‐treated infected wounds had significantly ( P < .05) lower bacterial counts at various time points than infected control wounds that had not been treated or had been treated with photosensitiser only or light only …”
Section: Resultsmentioning
confidence: 97%
“…The animal species used in the 19 studies were mice (n = 16) and rats (n = 3) . Of the 16 mouse studies, nine used BALB/c mice, 4 utilised Swiss albino mice, two used C57BL/ksj db/db mice, and one used CD1 mice . One study did not report the mouse strain that was used.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations